Early Perceptions, Enduring Consequences: How School Safety Concerns Shape Criminal Trajectories Through Developmental Pathways - Baltimore, Vaun (Journal of developmental and life-course criminology, 2025)
This study examines the relationship between school safety perceptions and criminal behavior, as well as the mechanisms that explain this relationship over the life course. Using data from Waves I, II, and V of the National Longitudinal Study of Adolescent to Adult Health (Add Health), we investigated the association between school safety concerns at Wave I and the odds of criminal offending in both the short term (Wave II, n = 10,079) and long term (Wave V, n = 6,921). Logistic regression analyses revealed that higher concerns about school safety were associated with 14% and 16% increased odds of criminal offending at Waves II and V, respectively. Mediation analyses further demonstrated that low school attachment, low self-control, and depressive symptoms partially mediated this association in the short term, while low self-control and attainment of a college degree partially mediated the long-term relationship. Our findings suggest that concerns about school safety can shape criminal trajectories via reduced self-control, lack of school attachment, increased psychological distress, and lower educational attainment. These results underscore the importance of fostering a sense of safety within educational environments to mitigate the risk of criminal offending both during adolescence and into adulthood.